THE INFLUENCE OF MOTIVATION AND WORK ENVIRONMENT ON WORK PRODUCTIVITY WITH TECHNOLOGICAL SUPPORT AS A MEDIATING VARIABLE (A STUDY ON ARCHIVIST EMPLOYEES AT BIRO UMUM SEKRETARIAT DAERAH PROVINSI BALI) - Anak Agung Sagung Intan Pratiwi; I Nengah Suarmanayasa (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the effects of training, motivation, and work environment on employee productivity, with technology support as a mediating variable. The research was conducted on archival officers at Biro Umum Sekretariat Daerah Provinsi Bali (General Bureau of the Regional Secretariat of Bali Province) using a quantitative approach. Data were collected through questionnaires and analyzed using path analysis to examine both direct and indirect effects among variables. The results show that training, motivation, and work environment each have a significant positive influence on productivity. Technology support significantly mediates the relationship between training and productivity, as well as between work environment and productivity, indicating that employees perform better when equipped with adequate technological tools and competencies. However, the mediating role of technology on the effect of motivation is less substantial. The study implies that improving digital infrastructure and providing continuous technology-based training are essential strategies for enhancing productivity in public-sector archival institutions.